O13.6. LONGITUDINAL TRAJECTORIES OF SOCIAL AND OCCUPATIONAL FUNCTIONING IN YOUNG PEOPLE WITH FIRST-EPISODE PSYCHOSIS IN COORDINATED SPECIALTY CARE. (9th April 2019) - van der Ven, Els; Pauselli, Luca; Scodes, Jennifer; Basaraba, Cale; Nossel, Ilana; Bello, Iruma; Wall, Melanie; Dixon, Lisa
Abstract: Background: Multicomponent programs for first-episode psychosis (FEP) offering coordinated specialty care (CSC) aim at maximizing opportunities for recovery by intervening early in the course of the illness. Two key components of recovery include social and occupational functioning. This study identified trajectories of social and occupational functioning in individuals enrolled in OnTrackNY, a statewide CSC program for treatment of early psychosis in community settings. Methods: The sample in this naturalistic cohort design included 634 individuals between ages 16 and 30 with recent-onset, non-affective psychosis with at least one CSC follow-up assessment at 20 different sites across New York State. Clinicians collected demographic and clinical data at program entry and quarterly up to one year. Social and occupational functioning were assessed using the MIRECC Global Assessment of Functioning scales.3 Growth mixture models (GMM) were used to identify subgroups of clients with similar social and occupational functioning trajectories. The association between baseline demographic variables and trajectories were tested using chi-square tests and one-way ANOVAs. Results: The GMM with four trajectory classes of social and occupational functioning best fit the data. The majority of the sample (59.1%) exhibited a greatly improving trajectory for occupational functioning from very low at baseline to moderate by 12 months with moderate and stable social functioning across the same period. A subgroup consisting of 14.9% of the sample had a similar moderate and stable trajectory for social functioning as the majority group, but were already exhibiting moderate occupational functioning at baseline and showed further improvement. Another subgroup (14.8%) entered the program high on both domains and remained stable or improved further. The most disabled group (11.4%) started low in both domains and improved across the year but remained at a dysfunctional occupational level. Female gender, higher education, adherence to antipsychotic medication and being employed or in school at enrollment were significantly associated with trajectories leading to more favorable social and occupational functioning. Discussion: Four identified trajectories of FEP patients enrolled in CSC had improving or high-stable social and occupational functioning patterns. This is in contrast with the long-held view that most individuals with psychotic disorders have a deteriorating course of illness. Most variability in terms of trajectory patterns over 1-year follow-up is observed in occupational functioning, which suggests that this may be an important domain to target for intervention.